Variations of the soft tissue thicknesses external to the ribs in Pectus Excavatum patients - Rodrigues, PL (2013)
BACKGROUND: Surgical repair of pectus excavatum (PE) has become more popular due to improvements in the minimally invasive Nuss procedure. The pre-surgical assessment of PE patients requires Computerized Tomography (CT), as the malformation characteristics vary from patient to patient. OBJECTIVE: This work aims to characterize soft tissue thickness (STT) external to the ribs among PE patients. It also presents a comparative analysis between the anterior chest wall surface before and after surgical correction. METHODS: Through surrounding tissue segmentation in CT data, STT values were calculated at different lines along the thoracic wall, with a reference point in the intersection of coronal and median planes. The comparative analysis between the two 3D anterior chest surfaces sets a surgical correction influence area (SCIA) and a volume of interest (VOI) based on image processing algorithms, 3D surface algorithms, and registration methods. RESULTS: There are always variations between left and right side STTs (2.54±2.05mm and 2.95±2.97mm for female and male patients, respectively). STTs are dependent on age, sex, and body mass index of each patient. On female patients, breast tissue induces additional errors in bar manual conception. The distances starting at the deformity's largest depression point at the SCIA are similar in all directions. Some diverging measures and outliers were found, being difficult to find similar characteristics between them, especially in asymmetric patients. CONCLUSION: The Nuss procedure metal bar must be modeled according to each patient's special characteristics. The studied relationships between STT and chest surface could represent a step forward to eliminate the CT scan from PE pre-surgical evaluation.